2006
DOI: 10.1007/s10592-005-7967-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of Chum Salmon (Oncorhynchus keta) Populations in the Lower Columbia River: Are Chum Salmon in Cascade Tributaries Remnant Populations?

Abstract: The lower Columbia River drainage once supported a run of over a million chum salmon. By the late 1950s, the run had decreased to often a few hundred fish. With the exception of Grays River near the coast and an aggregation of chum salmon spawning in creeks and the main stem near Bonneville Dam in the Columbia Gorge, most populations were thought to be extinct. However, chum salmon consistently return in low numbers to tributaries originating in the Cascade Range: the Cowlitz, Lewis, and Washougal rivers. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The practice of excluding loci, however, may be difficult to extend to large‐scale population studies because some populations may be free of null alleles at a given locus whereas other populations may have them. For example, in multiple samples of chum salmon Oncorhynchus keta (Walbaum 1792), taken from the Columbia River, U.S.A., no deviation from Hardy–Weinberg expectations at the SSR locus oke3 were observed (Small et al , ), whereas a strong deviation attributable to oke3 null alleles was observed in the Kuril Islands, Russia, O. keta (Kordicheva et al , ).…”
Section: Frequencies Of Null Alleles At Locus Oke3 That Were Revealedmentioning
confidence: 99%
“…The practice of excluding loci, however, may be difficult to extend to large‐scale population studies because some populations may be free of null alleles at a given locus whereas other populations may have them. For example, in multiple samples of chum salmon Oncorhynchus keta (Walbaum 1792), taken from the Columbia River, U.S.A., no deviation from Hardy–Weinberg expectations at the SSR locus oke3 were observed (Small et al , ), whereas a strong deviation attributable to oke3 null alleles was observed in the Kuril Islands, Russia, O. keta (Kordicheva et al , ).…”
Section: Frequencies Of Null Alleles At Locus Oke3 That Were Revealedmentioning
confidence: 99%
“…Several studies on the genetic structure of vertebrates have provided indications of the possible effects of natural and artificial dispersal on subpopulations of a particular species (Friesen et al 2006, Small et al 2006, McDevitt et al 2013. Other studies have shown the importance of habitat fragmentation and heterogeneity and the effects of genetic drift of subpopulations as a consequence of restricted dispersal (Bergl & Vigilant 2007, Heller et al 2010.…”
Section: Introductionmentioning
confidence: 99%